Solvent dielectric effect on electrochemical properties of 3,4-propylenedioxythiophene - Huner, Keziban; Sarac, Abdulkadir Sezai (INT ASSOC PHYSICAL CHEMISTS-IAPC, 2021)
The present study is focused on the electrochemical properties of poly(3,4-propylenedioxythiophene) (Poly(ProDOT)), electrocoated on the single carbon-fiber microelectrode (SCFME) in different electrolytic media, with different solvent dielectric constants (35.9, 41.7, 47.5, 53.3, 59.1 and 64.9). The highest deposition charge density of 24.49 mC cm(-2) and the highest specific capacitance of 23.17 mF cm(-2) were obtained for Poly(ProDOT) synthesized in a medium with the lowest solvent dielectric constant (epsilon = 35.9). Electrochemical impedance spectroscopy (EIS) results of Poly(ProDOT) coated SCFME measured at open circuit potential showed continuously increased impedance magnitudes as epsilon was increased from 35.9 to 59.1. For all films, almost capacitive impedance responses at lower frequencies at least were obtained. The highest capacitance was observed for the polymer film synthesized in the medium of epsilon = 35.9. The impedance of this film was also measured in different solvent mixtures with different dielectric constants at open circuit potential.
Keywords: carbon fiber; surface modification; electropolymerization; polythiophene derivate; electrochemical impedance spectra; 1-D POLYPYRROLE NANOFIBERS; CARBON-FIBER; POLY(3,4-ETHYLENEDIOXYTHIOPHENE) PEDOT; GLUCOSE-OXIDASE; IONIC LIQUID; BIOSENSOR; ELECTROSYNTHESIS; PERFORMANCE; ACID; Electrochemistry